The OV-TL 12/30 clone of anti-cytokeratin 7 antibody as a new marker of corneal conjunctivalization in patients with limbal stem cell deficiency - Jirsová, Kateřina; Dudaková, Lubica; Kalašová, Šárka; Veselá, Viera; Merjava, Stanislava (Investigative ophthalmology & visual science, 2011)
PURPOSE: To present cytokeratin (CK)7 (OV-TL 12/30 clone) as a newly identified, reliable marker for distinguishing between the conjunctival and corneal surface epithelia, which will contribute to the precise diagnosis of limbal stem cell deficiency (LSCD). METHODS: Corneal and conjunctival epithelial imprints from 12 cadaveric bulbi and from 9 patients with clinically diagnosed LSCD were used for CK7 and CK19 immunocytochemistry. Specimens on nitroacetate cellulose filter papers obtained from the patients were stained with a combination of periodic acid-Schiff (PAS) and Gill's modified Papanicolaou stains, to assess the presence of goblet cells (GCs). RESULTS: CK7 was present in almost all superficial conjunctival epithelial cells from the cadaveric specimens. No immunostaining was observed on the corneal surface. A prominent sharp border of stain was found between the positive conjunctiva and the completely negative epithelium of the central cornea. A more gradual centrifugal decrease in the number of positive cells between the conjunctiva and cornea was observed for CK19. Several CK19-positive cells were detected in the central corneal epithelium. All corneal specimens from affected eyes (unilateral as well as bilateral LSCD patients) revealed strong positivity for CK7, and GCs were present in only 78% of patients. CONCLUSIONS: In cases in which GCs are severely decreased or are absent from the conjunctival surface, the detection of CK7 (OV-TL 12/30 clone) clearly confirms the overgrowth of the conjunctival epithelium over the cornea. Moreover, CK7 is a more reliable marker for distinguishing between the corneal and conjunctival epithelia compared with CK19.
Keywords: Cadaver; Epithelium, Corneal; Corneal Diseases; Humans; limbus corneae; konjunktiva; dospělé kmenové buňky; lidé středního věku; Antibody Specificity; nemoci rohovky; Aged; dospělí; senioři; lidé; Biomarkers; Adult; rohovkový epitel; biologické markery; Middle Aged; protilátky; specificita protilátek; Aged, 80 and over; Antibodies; mrtvola; Keratin-7; Keratin-19; senioři nad 80 let; Adult Stem Cells; keratin-19; keratin-7; Conjunctiva; Limbus Corneae